Produtividade e composição bromatológica da Brachiaria decumbens após segundo ano de aplicação de dejetos de aves e suínos - Assis, Daniel Ferreira de (2007)
CHAPTER 2: Among the organic waste produced by poultry activity, the chicken manure presents potential to be used in the rehabilitation of degraded areas. The experiment was developed in RED LATOSSOL distrofic under grazing of Brachiaria decumbens in a state of advanced deterioration to evaluate the influence of fertilization and mineral with chicken manure in productivity, attributes bromatologics and in the absorption of nutrients from Brachiaria decumbens. The approach was mounted in completely randomized design, which were used six treatments (control without fertilization organic or mineral, control with mineral fertilization, four unique strengths of chicken manure (3,125, 6,250, 9,375 and 12,500 kg ha-1). The application of the residue the haul was in coverage, there were two collections the of Shoot of upland (December 2005 and February 2006). Observed that the influence of the application on productivity occurred only in 2 collection and was more expressive in dealing with 9,375 and 12,500 kg ha-1 of chicken manure. The behavior observed for CP, NDF ADF and lignin were little influenced by the organic fertilization or mineral, expecting that the crude protein were more influenced by fertilization depending on the content of nitrogen present in the chicken manure. The absorption of nutrients was more efficient for phosphorus and potassium, and was not significant for the calcium, magnesium, and sulfur, but it is recommended that sulfur is supplemented in another experiment with application of this waste. Concludes that the chicken manure presents potential to be used in pastures of Brachiaria decumbens, favoring its recovery function mainly in the levels of phosphorus and potassium. CHAPTER 3: The creation of turkey if has developed in Brazil mainly in the last decade, in virtue of the increase of the demand of the external and internal market. Despite the presented similarity the chicken manure enters and the turkey manure, is necessary to evaluate particularities of this residue in the recovery of an area degraded under pasture vegetation. The experiment was developed in a dystrophic RED LATOSSOLO under pasture of Brachiaria decumbens in advanced state of degradation to evaluate the influence of the mineral fertilization and the turkey manure in the chemical attributes of the ground, and in the absorption of nutrients and the bromatologic characteristics of the Brachiaria decumbens. The delineation was mounted in completely randomized design, where six treatments had been used (witness, a mineral dosage, four exclusive dosages of turkey manure (1,695; 3,390; 5,085 and 6,780 kg ha-1). The application of the residue was the throwing in covering, became fulfilled two collections leaf in the period of waters. It presents itself as an excellent organic residue to promote the recovery of degraded areas despite its bigger increments have been on levels of phosphorus and potassium. It was hoped that the turkey manure it is larger increments in productivity of DM and crude protein, which has not occurred, indicating the need for more research and use of this residue. CHAPTER 4: Objective to evaluate the influence of fertilization mineral and liquid swine slurry in productivity, bromatológic and absorption of nutrients from Brachiaria decumbens. The experiment was developed in a LATOSSOLO RED distrofic under grazing of Brachiaria decumbens, in a state of deterioration with evolutionary loss of vigor and productivity of forage, advanced. The approach was mounted in completely randomized design with six treatments (control without fertilization, control with the use of mineral fertilizer, four unique strengths of liquid swine slurry (60 m3 ha-1, 121 m3 ha-1, 181 m3 ha-1 and 241 m3 ha-1). The application of the residue was done to haul in coverage, took place two applications of waste separate and two collections of leaf material (December 2005 and February 2006). Noted that the liquid swine slurry promoted increases in productivity of dry matter and the green pasture. However not promoted any improvement in the absorption of nutrient evaluated. The liquid swine slurry also promoted reduction in the content of the forage ADF. It is recommended greater care in the characterization of excrements in experimentation, and conditions this experiment their application not caused environment impact to the system.